Fostering Autonomy through Digital Reading: Students’ Evaluation of the ReadyRead Application - Rulli Putri Maulidia; Fransisca Maria Ivone; Anik Nunuk Wulyani (Jurnal Pendidikan Humaniora, 2020)
Abstract: ReadyRead is an Android-based application which provides several features for scaffolding reading comprehension practice. It is the product of Design-Based Research. The present study examined high school students’ experience in using the application. An online questionnaire was employed to gather information on students’ opinions regarding the content, learning activities, and usability of the app. Results of the data analysis revealed the most favorable feature in the app perceived to be the most helpful for students in learning reading independently. Further, the app provides space for students to learn individually and collaboratively. Suggestions from the students are constructive and taken into account in the further development and sustainability of the app.Keywords: digital reading, reading application, autonomy, evaluation Abstrak: ReadyRead merupakan aplikasi membaca yang menyediakan fitur-fitur untuk mendukung pembelajaran membaca. Artikel ini meneliti pengalaman siswa SMA selama menggunakan aplikasi tersebut. Kuisioner daring digunakan untuk mengumpulkan informasi terkait pendapat siswa tentang isi, aktivitas dan penggunaan aplikasi. Hasil data analisis mengungkapkan bahwa fitur yang disukai siswa adalah fitur yang dirasa sangat membantu siswa untuk belajar secara mandiri. Selain itu, aplikasi ini juga memberikan ruang untuk siswa belajar secara kolaboratif selain belajar secara individu. Masukan dari siswa sangatlah membangun untuk pengembangan dan keberlanjutan aplikasi ReadyRead.Kata kunci: membaca digital, aplikasi membaca, kemandirian, evaluasi